Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Model Pembelajaran Student Facilitator and Explaining (SFAE) pada Pembelajaran Matematka Kelas VIII SMPN 2 Ampek Angkek Tahun Pelajaran 2021/2022 - Indrayani Indrayani; Rusdi Rusdi; Haida Fitri; Tasnim Rahmat (Journal on Education, 2023)
This research is motivated by the problems found in class VIII of SMPN 2 Ampek Angkek, namely textbooks are the only source of learning for students. and the limited number of book packages means that not all students have a book package as a guide and guide in understanding lessons and learning only goes in one direction and is the size of the teacher. Thus, making the learning outcomes of students low. to overcome this problem, teachers must have companion learning resources that can be used in the learning process, one of which is the Student Worksheet (LKPD). The designed LKPD is Student Facilitator and Explaining (SFAE) model-based LKPD. This study aims to obtain a valid, practical and effective Student Facilitator and Explaining (SFAE) model-based LKPD product in class VIII SMPN 2 Ampek Angkek. This research is a developmental research or Research and Development (R&D) with the Sugiyono development model. The steps that researchers use are as follows. (1) potential and problems, (2) information gathering, (3) product design, (4) design validity, (5) improvement design, and (6) trials Based on the development research that has been carried out, it is obtained that LKPD has a very valid criterion of 83.4% for practicality, 86.26% for practicality, and 86.26% for effectiveness the very effective criterion is 83%. So it can be concluded that the Mathematics LKPD Based on the Student Facilitator and Explaining (SFAE) Learning model) In Class VIII Mathematics Learning at SMPN 2 Ampek Angkek that is developed is valid, practical, and effective.